A case series comparison of semantically focused vs. phonologically focused cued naming treatment in aphasia. - Neumann, Yael (Clinical Linguistics & Phonetics, 2018)
There is a lack of clarity in the field regarding how to best predict which naming treatment will be most beneficial for a particular individual with aphasia. The purpose of this study was to elucidate whether or not semantic or phonological therapy differentially impacts on outcomes for people with a range of different aphasic profiles when given both therapies. A single-participant design, with multiple repeated baselines for naming, replicated across four participants, was used. Participants were provided with a counterbalanced order of Semantic Feature Analysis (SFA) and Phonological Components Analysis (PCA) treatment. Findings demonstrated differential effects across participants. This seemed to be influenced by factors such as severity of anomia, order of treatment presentation, and capacity limits. Clinical implications of these findings highlight the importance of expanding our picture of a participant’s behaviours to consider what other important factors can inform intervention decisions.